2020
DOI: 10.33314/jnhrc.v18i1.2602
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Cases of COVID-19 in Far Western Province of Nepal

Abstract: The novel coronavirus (COVID-19) cause various symptoms such as pneumonia, fever, breathing difficult and lung infection. Till now, total 9 cases are reported in Nepal and 4 cases from this province. This case series is to describe the initial clinical features of COVID-19 among the patients admitted in isolation ward of Seti Provincial Hospital. Oropharyngeal swab was taken from all four patients and sample was transfer to national reference laboratory. Three patients were coming from infected country and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The earliest data to emerge from across the world have consistently described patients who have presented with a milder illness and have rapidly recovered [9,[15][16]. Kim et al observed 213 COVID-19 patients in South Korea and found that 19% remained asymptomatic [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest data to emerge from across the world have consistently described patients who have presented with a milder illness and have rapidly recovered [9,[15][16]. Kim et al observed 213 COVID-19 patients in South Korea and found that 19% remained asymptomatic [14].…”
Section: Discussionmentioning
confidence: 99%
“…Others had a cough (40%) and hypoxia (40%). Joshi et al described nine relatively younger men in a small case series from Nepal who had a mean age of 20 -40 years [15].…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence also might not represent national level prevalence as samples from random populations have not been tested. Early studies reported that COVID-19 patients in Nepal showed few or no symptoms at all (24,36). The situation updates of the Ministry of Health and Population (MoHP) also indicates that most of the confirmed cases are found through active surveillance and contact tracing rather than patients visiting hospitals with symptoms (25).…”
Section: Discussionmentioning
confidence: 99%
“…1.1% of the cases were symptomatic and were in isolation, death was reported to be among 1.1% of the COVID 19 patients [13]. According to research performed by Joshi J et al on the clinical profile of COVID 19 patients in the far Western province (Sudurpashchim Pradesh) of Nepal showed that the patients who were COVID-19 positive were generally males and that they were between 20-40 years in age [23]. This is highly varied from findings in China as according to a study conducted in China proved the average age of the COVID-19 cases to be 55•5 years [24].…”
Section: Age Of the Covid-19 Positive Patients In Nepal Vs Global Datamentioning
confidence: 99%
“…According to research performed by Joshi J et al on the clinical profile of COVID 19 patients in the far Western province (Sudurpashchim Pradesh) of Nepal it became evident that the majority of these COVID-19 positive cases were male; superimposed to this was the fact that these males were between 20-40 years in age [23]. According to a report published by the Ministry of Health and population, May 22, 2020, It was stated that bulk of the cases were of the ages between 21 to 30 years.…”
Section: Age Of Covid 19 Positive Patients In Nepalmentioning
confidence: 99%